Ant diversity and composition patterns along the urbanization gradients in an arid city. Issue 39 (18th October 2021) - Abdel-Dayem, Mahmoud S.; Sharaf, Mostafa R.; Majer, Jonathan D.; Al-Sadoon, Mohammed K.; Aldawood, Abdulrahman S.; Aldhafer, Hathal M.; Orabi, Gamal M.
ABSTRACT: The dramatic increased rates of uncontrolled urbanisation in various parts of the World have resulted in loss of native species and overall threats to biodiversity. Over the last few decades Saudi Arabia has witnessed a remarkably rapid population growth and unparalleled levels of urbanisation, leading to threats to biodiversity. In this study we focused on arid city (Riyadh, Saudi Arabia) where ant assemblages cross an urban-rural gradient. Ants were collected by pitfall traps from 15 sites along three different urbanisation gradients at 3-monthly intervals throughout 1 year. Ant abundance, species richness, evenness, and α diversity were consistent across the urbanisation gradient. However, significant differences were observed in ant β diversity and assemblage composition between rural and urban, suburban and urban, but not between rural and suburban sites. Eleven ant species were identified as indicator species (IV values between 50.7% and 80.7%). These ant assemblages were influenced by flora, ground cover, soil variables, and urbanisation characteristics. To conclude, we found a significant effect of urbanisation on the β diversity and composition of ant assemblages.